Proposed Enrollment System for Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The enrollment system is one of the most important systems in university and lower levels of education. An enrollment record ensures good data management of enrollee information. It also encourages possible enrollees to matriculate in the institution. The purpose of the enrollment system is to enable students to enroll in their subjects before the commencement of their semesters. Students increase every year, and the difficulty of the enrollment procedure also increases. The amount of information that needs to be collected also increases. The systems development life cycle method was utilized in this research. In the planning stage, the researchers gathered information by interviewing the client. In the analysis phase, the team analyzed the problems that are encountered by the client in the enrollment process and then the planned to solve this problem and provide a solution. In the design stage, the project team provided the layout and flowchart of the proposed system. Afterward, in the testing stage, the user tested the system if the system is working as intended and compatible with the computer. In the maintenance stage, the project team maintains the system whenever it malfunctions. The results showed that the system was working as intended. This system had a three-attempt login function, which increased the security of the data. The system also allowed data manipulation such as enrolling students, deleting student information, and updating student information. The data process was also monitored in a separate form for the admin, thereby enabling the monitoring of the system users. The students who participated in this system focused on how they will use it or what the function is. The process focused on the administration because the system is not fully functional, but other tools are extremely useful, safe, and user-friendly; you can input your data and your important information. Other participants of this system can use and test if it is useful in the future. The result showed that the system should be upgraded for the students because the enrollment system focused on the admin side and not on the student side. Therefore, the proposed system is extremely useful, safe, and user-friendly that can also help the administrators and the school.
Keywords: evident, utilized, manipulation